1992
DOI: 10.1007/bf01888524
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal lymphangiectasia: Evaluation by CT and scintigraphy

Abstract: Intestinal lymphangiectasia caused severe diarrhea and generalized edema in a 40-year-old man. The diagnosis was established by clinical, laboratory, and duodenal biopsy findings. The abnormalities detected on computed tomography (CT) and scintigraphy using 99mTc human serum albumin are herein described and pertinent literature is briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 3 publications
2
16
1
1
Order By: Relevance
“…99m Tc human serum albumin has been used successfully to image PLE. 10,[13][14][15] However, it is not an ideal radiotracer. Problems have been reported with in vivo chemical stability, with marked dissociation documented over 24 hours, 35 with variable radiolabelling efficiency even within the one batch, with reduced specificity as up to 30% of the activity is in the free or reduced form, and with significant radiation burden on the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…99m Tc human serum albumin has been used successfully to image PLE. 10,[13][14][15] However, it is not an ideal radiotracer. Problems have been reported with in vivo chemical stability, with marked dissociation documented over 24 hours, 35 with variable radiolabelling efficiency even within the one batch, with reduced specificity as up to 30% of the activity is in the free or reduced form, and with significant radiation burden on the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Several radiopharmaceuticals have been used, including indium-111 ( 111 In) -transferrin 12 and technetium-99m ( 99m Tc)-human serum albumin. 10,[13][14][15] However 99m Tc-dextran appears to be superior as it is a more chemically stable compound, provides a higher target to-background activity ratio, and false-positive studies are less likely. 16 It has been reported that intestinal lymphangiectasia and PLE may respond to small bowel resection where the disease process is confined to a relatively small segment of the bowel.…”
mentioning
confidence: 99%
“…A wide variety of radionucleotides have been used for this purpose, including technetium (Tc)-99 m-human serum albumin and other Tc-99m-labeled substances, as well as 111In transferrin (Saverymuttu et al, 1983;Puri et al, 1992;Bhatnagor et al, 1995a;Chiu et al, 2001). These techniques do yield positive scintigraphs in cases of PLE, but it is not clear that they are sensitive enough to pick up low-level abnormalities; in addition, although these techniques can conceivably provide rough estimates of the severity of PLE, they are not truly quantitative.…”
Section: Results Of Metabolic Studiesmentioning
confidence: 99%
“…Finally, the advent of scintigraphy (Saverymuttu et al, 1983;Puri et al, 1992;Bhatnagor et al, 1995b) has opened the possibility of identifying the presence of a localized lymphatic abnormality in a particular segment of the bowel and, thus, the possibility of surgical treatment of the IL (Kinmonth and Cox, 1974;Fox and Lucani, 1993;Persic et al, 1998;Kim et al, 2009). Suffice it to say that the efficacy of this approach has yet to be clearly proved.…”
Section: Diagnosis and Treatmentmentioning
confidence: 94%
See 1 more Smart Citation